Perencanaan Hidrolika Pemboran Trayek 12-1/4” dan 8-1/2” Pada Sumur NT Lapangan DZ - Citra Wahyuningrum; Eko Prastio; Bismaka Daniswara (Jurnal Bhara Petro Energi, 2025)
In this study we plan the development wells in Trayeks 12 ¼ and 8 ½. As we all know, drilling mud is one of the indicators of the success or failure of a drilling operation. In the previous well, the drilling fluid was not optimal so that the cuttings were deposited which had the potential to cause problems in the drilling operation, namely pipe sticking. In the drilling hydraulics planning for the NT well in the DZ field, the cuttings were optimized using the Horse Power Per Square Inch (HSI) approach. HSI calculations are carried out to determine the efficiency of the hydraulic system by considering the main parameters such as pump pressure, Total Flow Area (TFA), Pressure Loss at Bit (Pbit), Impact force at Bit (BiF), Nozzle Velocity (Vn). In Trayek 12 ¼ inch, the HSI value obtained was 3,2hp/in2, thus maximizing the efficiency of hole cleaning, while in Trayek 8 ½ inch, the HSI value obtained was 2,7hp/in2, thus providing optimal bit penetration. The results of the HSI calculations provide guidance to reduce the possibility of operational problems, such as pipe sticking or loss of circulation, which often occur in drilling operations in the DZ field.